My Dream World - Miettinen, Satu (Lapin yliopisto taiteiden tiedekunta, 2014)
Arktikum museum Rovaniemi, Finland 16.4.-12.5.2014, Open Design week the Attic, City Hall, Cape Town, South Africa, the project was recognized as an official part of World Design Capital Cape Town 2014 program 11.-23.8.2014 Helina Rautavaaran museo Espoo, Finland 4.-31.3. 2015 Kirjasto 10 Helsinki, Finland 16.-31.3.2015